Penyuluhan Kesehatan Dalam Menjaga Kebersihan Kulit Di Sekolah Dasar Negeri 27 Cakranegara - Hasbi, Nurmi (Universitas Mataram, 2023)
The skin is an organ that functions as the main protector of the human body from the outside environment, as well as its role in receiving stimuli and responding to these stimuli. Skin diseases can be caused by various factors such as fungi, viruses, germs, and parasites that infect or interfere with skin health. Diligent cleaning of the body, keeping clothes clean, and taking care of the surrounding environment can help prevent infections and other skin problems. Knowledge of personal hygiene or personal hygiene has a very important role in the growth and development of a child, because elementary school-age children aged 6 to 11 years have bodies that are vulnerable to health problems. This service aims to provide knowledge to elementary school students. about how to maintain personal hygiene to avoid skin infections. These community service partners are students of SDN 27 Cakranegara, Mataram, NTB. The method used in this service is a lecture-based extension method and interactive dialogue. The dedication participants looked enthusiastic and happy with this theme. Hopefully this service activity will succeed in achieving its goals and have a positive impact on students and the surrounding community